Sustainable wheat gluten foams with self-expansion and water/blood-triggered shape recovery. (April 2023) - Chen, Tuying; Tang, Yingzi; Zhao, Huijing; Zhang, Keqin; Meng, Kai
A cheap and easily obtainable wheat gluten (WG) was used to fabricate bio-foams via a simple method of stirring, heating, and lyophilization. The foam possesses a 3D layered porous structure with interconnected channels, and the biofoam has excellent mechanical properties through glycerol plasticization and glutaraldehyde (GA) cross-linking. The water absorption and volume expansion rate can reach 793.67 ∼ 918.45% and 201.47 ∼ 239.53% respectively. In dry state, the foams had good compression resilience, and can basically recover its original shape after withstanding 60% compression strain for about 7 h. In wet state, they can withstand 10 cycles of compression test, and had good compressive resilience and durability; they also had fast liquid-triggered shape recovery performance, of which the foams can reabsorb liquid, expand, and recover its original shape within 40 seconds after withstanding 80% compression strain. In addition, The hemolysis rates of red blood cells treated with 1, 3, and 5 mg/mL of 14WG-20g-5GA foam suspension were 0.53 ± 0.12%, 2.12 ± 0.34%, and 3.97 ± 0.21%, respectively, all of which were below the permissible range for biological materials (<5%). The above-mentioned advantages made the sustainable foams be potentially useful for medical dressings, especially for the treatment of non-compressible haemorrhaging, which offered a new field of application for WG protein and its added value was also increased obviously.